2020
DOI: 10.1080/21691401.2020.1813743
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminolevulinic acid hydrochloride loaded microbubbles-mediated sonodynamic therapy in pancreatic cancer cells

Abstract: 5-Aminolevulinic acid hydrochloride (ALA)-mediated sonodynamic therapy (SDT) had anti-tumour effect on pancreatic cancer cells. Hence, ALA loaded lipid/poly(lactic-co-glycolic acid) (PLGA) microbubbles (MBs)-mediated SDT for pancreatic cancer has great potential. The average size of ALA-lipid MBs and ALA-PLGA MBs was about 3.0 mm. The two kinds of MBs had good biocompatibility to normal HPDE6-C7 cells and were not toxic to pancreatic cancer cells. Compared with ALA-induced SDT, a statistically significant decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“… 124 Additionally, hyperthermic cells can also be killed by a non-thermal effect (cavitation and direct effect) of US under various gas conditions. 125 Yang et al 126 reported that compared with SDT alone, SDT combined with 5-ALA mediated hyperthermia could inhibit the growth of human glioma more effectively by in vitro and in vivo experiments. As a new kind of light and sound responsive nanomaterial, ALA-lipid/PLGA MB-mediated SDT was a promising treatment for pancreatic cancer.…”
Section: Sdt-based Synergistic Therapymentioning
confidence: 99%
“… 124 Additionally, hyperthermic cells can also be killed by a non-thermal effect (cavitation and direct effect) of US under various gas conditions. 125 Yang et al 126 reported that compared with SDT alone, SDT combined with 5-ALA mediated hyperthermia could inhibit the growth of human glioma more effectively by in vitro and in vivo experiments. As a new kind of light and sound responsive nanomaterial, ALA-lipid/PLGA MB-mediated SDT was a promising treatment for pancreatic cancer.…”
Section: Sdt-based Synergistic Therapymentioning
confidence: 99%
“…It should be noted that in the absence of hyperthermia treatment of the tumours, their non-liposomal doxorubicin concentration was approximately eight times higher than that when liposomal doxorubicin was used (parameters: f = 1.2 MHz, Power = 7 W, d.c = 100%, T = 41.2 ± 1.3 • C) [174]. Additional studies have shown that the delivery of gemcitabine to pancreatic tumours was enhanced by sonoporation in human pancreatic MiaPaCa-2 tumours grown orthotopically in mice [175], while the combination of sonodynamic therapy with various anti-cancer compounds, including 5-aminolevulinic acid [176,177], 5FU [178,179], antibiotic and root extracts [180], gemcitabine [181], nanocomposites able to generate reactive oxygen species or nitric oxide [182][183][184], radiation [185] and epirubicin [186], have provided proof of concept for the intriguing potential that sonodynamic therapy has in pancreatic cancer.…”
Section: Drug Delivery and Sonodynamic Therapy Studies In Preclinical...mentioning
confidence: 99%
“…5-Aminolevulinic acid hydrochloride (ALA) is an effective sonosensitizer. Yang and colleagues indicated that ALA-loaded lipid/poly(lactic-co-glycolic acid) (PLGA) microbubble (MB)-mediated SDT induces the pyroptosis of AsPC-1 and BxPC-3 cells because the combination of MBs and ultrasound can facilitate cell membrane permeability and cause cell swelling ( 88 ).…”
Section: The Potential Of Pyroptosis In Pdac Treatmentmentioning
confidence: 99%